Diabatic visualization shows effects of micro-fins on evaporation of R410A: Smooth, axial micro-fin, and helical micro-fin tubes. (April 2020) - Yang, Cheng-Min; Hrnjak, Pega
Highlights: Flow boiling in a transparent micro-fin tube is visualized under diabatic conditions. Comparison of flow patterns in smooth, axial micro-fin and helical micro-fin tubes. Bubbles are mainly generated in the groove region due to higher superheat. Liquid slug influences the nucleation sites at the upper part of the micro-fin tube. Bubbles in the helical micro-fin tube are easier to merge. Abstract: A novel approach to visualize the flow boiling inside a clear micro-fin tube under diabatic conditions is presented. Transparent smooth, axial micro-fin, and helical micro-fin tubes are made by 3D printing. The 3D printed tube is placed inside a glass tube and heated by the transparent secondary fluid flowing between the two tubes for providing the evaporation conditions and transparency. R410A flow boiling and the flow patterns in the three geometries captured with a high speed camera are compared. The experimental results show that micro-fin geometry influences flow behavior. Bubbles are mainly generated in the groove region due to a higher superheat than the fin region. Some of the liquid refrigerant is trapped in the grooves of the upper part of the micro-fin tube when the slug flow is present, and bubbles are generated in this thin liquid layer. In addition, the bubbles in the helical micro-fin tube are easier to merge because of the obstacle of the fin geometry for the bubble flowing path. As the two bubble merge, the conversion of surface free energy causes the bubble to travel with a higher velocity.